Coronaviridae (Virus Taxonomy, 2012)
This chapter focuses on Coronaviridae family whose two subfamilies include Coronavirinae and Torovirinae. The member genera include Alphacoronavirus, Betacoronavirus, Gammacoronavirus, Torovirus, and Bafinivirus. The members of the family Coronaviridae are enveloped and positive stranded RNA viruses of three classes of vertebrates, which include corona- and toroviruses for mammals, coronaviruses for birds, and bafiniviruses for fishes. The nucleocapsids are helical and can be released from the virion by treatment with detergents. Where the coronavirus nucleocapsid appears to be loosely wound, those of the Torovirinae are distinctively tubular. The entire replication cycle takes place in the cytoplasm and involves the production of full-length and subgenome-sized (sg) minus-strand RNA intermediates with the viral genome serving both as mRNA for the replicase polyproteins and as a template for minus-strand synthesis. Members of the family Coronaviridae all seem to share two envelope protein species, the membrane (M) and spike (S) proteins. Similarities in size, predicted structures and presumed function(s) suggest a common ancestry, and the remote, but significant sequence similarities observed for toro-, bafini-, and (to lesser extent) coronavirus S proteins lend further support to this view. The replicase polyproteins of the Coronaviridae comprise a number of characteristic domains arranged in a conserved order.